Diamond compact assembly block for coal field and compact preparation method
By adopting ring structure assembly blocks and new preparation technology, the problems of unstable surface quality and low production efficiency of diamond composite sheets for existing coal fields are solved, and a more efficient preparation process and better composite sheets are achieved.
Patent Information
- Application Number
- CN202411659495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The existing diamond composite sheet assembly blocks for coal fields have defects such as unstable surface quality, pits, cracks, and stratification, and low production efficiency and long preparation time.
The composite sheet is prepared through the high-temperature and high-pressure sintering process by using ring structure assembly blocks and new preparation technology, including wax stone blocks embedded with lined tubes, pressure stabilization tubes, ring heating tubes, isolation tubes and metal tubes.
The surface quality of the composite sheet is improved, the production efficiency is improved, the preparation time is shortened, and a more balanced sintering temperature and pressure range is achieved.
Smart Images

Figure CN119501069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of diamond composite sheet processing, and in particular to a diamond composite sheet assembly block for coal fields and a composite sheet preparation method. Background Art
[0002] With the gradual reduction and disappearance of shallow resources, the mining depth of coalfields and mines is getting deeper and deeper. The mining depth continues to increase, and the geological conditions are more complex. Diamond composite sheets for coalfields have replaced cemented carbide on a large scale and are used in mine drill bits. At present, a single assembly block of diamond composite sheet manufacturers can only synthesize 1 or 2 composite sheets, and the preparation time is as long as 15-30 minutes. Although the demand for diamond composite sheets for coalfields is large, its production cost needs to be strictly controlled to meet market demand. The main problems with the current assembly blocks and preparation technology are unstable surface quality, pits, cracks, delamination and other defects often occur, low product production efficiency, and long preparation time. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a diamond composite sheet assembly block and a composite sheet preparation method for coal fields. The present invention utilizes a ring structure assembly block and a new preparation technology, which not only improves the surface quality of the composite sheet, but also improves production efficiency.
[0004] The objective of the present invention is achieved through the following measures: a diamond composite sheet assembly block for coal fields, comprising a talc block embedded with an inner lining tube, a voltage-stabilizing tube is installed inside the inner lining tube, a ring-type heating tube is installed inside the voltage-stabilizing tube, 3-5 heating cavities are opened inside the ring-type heating tube, and each heating cavity is installed with an isolation tube, a metal tube for placing a core body is installed inside the isolation tube, a heating plate, a metal plate, a boosting ring, and a sealing ring are sequentially arranged at the upper and lower ends of the inner lining tube from the inside to the outside, a conductive steel ring is arranged inside the boosting ring and the sealing ring, and an alloy pad for conductive use is arranged at the outer end of the conductive steel ring.
[0005] Preferably, the pyrophyllite block is composed of pyrophyllite particles and a ceramic binder. The pyrophyllite powder is crushed to below 100 mesh, 5%-10% of a hydrophilic ceramic binder is added, and the block is pressed by a 100T-150T four-column hydraulic press at 30-50MPa and maintained at a pressure of 30s, and then baked in a high-temperature oven at 200°C-800°C for 5h to form the block.
[0006] Preferably, the inner liner pipe is made of 60-90 parts of dolomite powder, 10-20 parts of MgO powder, and 10-20 parts of Al2O3 powder, by pressing with a four-column hydraulic press at 5MPa and maintaining the pressure for 30s.
[0007] Preferably, the voltage-stabilizing tube is a three-section tube, the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
[0008] Preferably, the annular heating tube is formed by one-step molding and pressing of scaly graphite with a purity greater than 99.9% and a mesh size less than 40.
[0009] Preferably, the isolation tube is made of 50-70 parts of NaCl powder less than 100 mesh, 3-5 parts of Al2O3 powder less than 200 mesh, 3-5 parts of ZrO2 powder less than 200 mesh, 3-5 parts of SiC powder less than 200 mesh, and 0.5-2 parts of resin binder.
[0010] Preferably, the metal tube is made of 10-15 parts of 1um-10um Ni powder, 10-20 parts of 10um-50um Zr powder, 10-20 parts of 10um-50um Fe powder, 5-10 parts of 10um-50um Mn powder, and 5-10 parts of 10um-50um Mo powder, and the mixed powder is hot-pressed and sintered at 1300-1800°C for 30-70 minutes.
[0011] Preferably, the heating plate is formed by pressing and molding once from flake graphite with a purity of more than 99.9% and a size less than 40 meshes;
[0012] The metal sheet material is made of three metal powders of Ti, Mo and Cr with contents of 60%, 25% and 15% respectively, and is sintered at 1300-1800°C for 30-70 minutes.
[0013] The booster ring is made of 70-90 parts of Al2O3, 10-20 parts of SiC, and 0.5-1 parts of a binder, and is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s;
[0014] The sealing ring is made of 50-70 parts of pyrophyllite powder, 10-20 parts of dolomite powder, 5-10 parts of clay powder and 0.5-1 part of binder, and is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s.
[0015] Preferably, the conductive alloy pad is made of recycled hard alloy top hammer material, which is ball-milled to 5-10um, pre-pressed, and sintered at 1300℃-1500℃ for 10-15min.
[0016] The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
[0017] The method for preparing a composite sheet by using the above-mentioned diamond composite sheet assembly block for coal fields is used to place the core body into the heating cavity of the assembly block. Each heating cavity can hold 4 core bodies, and the core bodies are separated by spacers, and one spacer is placed at each end of the outermost core body. The assembly block is placed in a six-sided top press for heating;
[0018] In the first stage, the temperature is heated to 300-400℃ for 10-50s and kept warm for 10-60s; the apparent pressure increases from 0MPa to 50-70MPa;
[0019] The second stage is heating to 800-1000℃ for 10-50s and keeping warm for 10-60s; the apparent pressure is maintained at 80-10SMPa;
[0020] In the third stage, the temperature drops rapidly to 200-300℃ within 1-5s and is kept warm for 10-60s; the apparent pressure is maintained at 80-10SMPa;
[0021] The fourth stage is heating to 1500℃-1800℃ for 10-60s and keeping warm for 100-150s; the apparent pressure is maintained at 80-105MPa;
[0022] In the final stage, the heating is stopped and the temperature is lowered for 180-240 seconds; the pressure is slowly reduced, the pressure is released, the assembly block is taken out, and the prepared composite sheet is taken out from the assembly block.
[0023] The beneficial effects of the present invention are as follows: the new pyrophyllite block used in the present invention, compared with the traditional pyrophyllite block, the added hydrophilic ceramic binder can absorb more free water molecules at high temperature and high pressure, and can inhibit the phase change of the pyrophyllite phase structure; 3-5 heating cavities can hold 12-20 cores, which is more than 6 times more efficient than the traditional single-cavity production efficiency; the mixed powder metal tube can absorb more impurities when an oxidation reaction occurs at high temperature and high pressure, thereby playing a role in purifying the atmosphere; the new preparation technology can make the assembly faster, the temperature range and pressure range more balanced within a shorter sintering time, and the sintering more stable, so as to achieve the purpose of improving surface quality, production efficiency, and shortening preparation time. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the assembly block structure;
[0025] Figure 2 A schematic diagram of the core placement is shown;
[0026] Figure 3 It is a cross-sectional view of the assembly block;
[0027] Figure 4 It is a schematic diagram of the composite sheet processing process;
[0028] In the figure: 1- talc block, 2- sealing ring, 3- boost ring, 4- metal sheet, 5- voltage regulator tube, 6- ring heating tube, 7- isolating tube, 8- metal tube, 9- heating plate, 10- conductive steel ring, 11- conductive alloy pad, 12- lining tube, 13- isolating plate, 14- core body. DETAILED DESCRIPTION
[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] like Figure 1 , Figure 2 , Figure 3 As shown, a diamond composite sheet assembly block for coal fields includes a talc block 1 with an inner lining tube 12 embedded therein, that is, the talc block 1 has an inner lining tube 12 inside, a voltage-stabilizing tube 5 is installed inside the inner lining tube 12, an annular heating tube 6 is installed inside the voltage-stabilizing tube 5, 3-5 heating cavities are opened inside the annular heating tube 6, and each heating cavity is installed with an isolation tube 7, and a metal tube 8 for placing a core 14 is installed inside the isolation tube 7, and 12 cores can be placed in each metal tube, and each core needs to be separated by an isolation sheet 13, and isolation sheets 13 also need to be placed on the outer ends of the top and bottom cores, and heating sheets 9, metal sheets 4, boosting rings 3, and sealing rings 2 are installed in sequence at the upper and lower ends of the inner lining tube from the inside to the outside, and conductive steel rings 10 are installed in the boosting ring 3 and the sealing ring 2, and conductive alloy pads 11 are installed at the outer ends of the conductive steel rings.
[0031] The assembly block uses a new type of raw material, which is described in detail below:
[0032] Example 1: The pyrophyllite block is composed of pyrophyllite particles and a ceramic binder. The pyrophyllite powder is crushed to less than 100 meshes, 5% of a hydrophilic ceramic binder is added, and the pyrophyllite block is pressed by a 100T four-column hydraulic press at 30MPa and a pressure of 30s, and then baked in a high-temperature oven at 200℃ for 5h to form. The pyrophyllite block adopts a new formula technology different from the prior art. Compared with the traditional pyrophyllite block, the added hydrophilic ceramic binder can absorb more free water molecules at high temperature and high pressure, and can inhibit the phase change of the pyrophyllite phase structure.
[0033] The liner pipe is made of 60Kg dolomite powder, 10Kg MgO powder and 10Kg Al2O3 powder, which are pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s.
[0034] The voltage regulator tube is a three-section tube, the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
[0035] The ring-shaped heating tube is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0036] The isolation tube is made of 50Kg of NaCl powder less than 100 mesh, 3Kg of Al2O3 powder less than 200 mesh, 3Kg of ZrO2 powder less than 200 mesh, 3Kg of SiC powder less than 200 mesh, and 0.5Kg of resin binder. The traditional isolation tube is made of NaCl as raw material. The new isolation tube can not only cool down the pressure, but also add Al2O3, ZrO2, and SiC refractory materials to NaCl to reduce the displacement of the isolation tube under high temperature and high pressure, so that the pressure transmission is more sufficient.
[0037] The isolation sheet is made of the same materials as the isolation tube, which is made of 50 kg of NaCl powder less than 100 mesh, 3 kg of Al2O3 powder less than 200 mesh, 3 kg of ZrO2 powder less than 200 mesh, 3 kg of SiC powder less than 200 mesh, and 0.5 kg of resin binder. The isolation sheet plays an isolating role between the cores, and the added refractory material plays a pressurizing role.
[0038] The metal tube is made of 10Kg of 1um-10um Ni powder, 10Kg of 10um-50um Zr powder, 10Kg of 10um-50um Fe powder, 5Kg of 10um-50um Mn powder, and 5Kg of 10um-50um Mo powder. The mixed powder is hot-pressed and sintered at 1300℃ for 30 minutes. The metal tube contains Ni, Zr, Fe, Mn, and Mo elements, which are very easy to oxidize under high temperature and high pressure. They can absorb more oxygen and other impurities in the assembly cavity, reduce the oxidation reaction between impurities and the core, and make the surface quality more stable.
[0039] The heating plate is made of flake graphite with a purity of more than 99.9% and less than 40 meshes, and is pressed in one step; it mainly provides auxiliary heating at both ends of the annular heating tube, so that the middle layer core and the cores at both ends are heated more evenly.
[0040] The metal sheet material is made of three metal powders, Ti, Mo, and Cr, with contents of 60%, 25%, and 15% respectively, and is sintered at 1300°C for 30 minutes.
[0041] The booster ring is made of 70Kg Al2O3, 10Kg SiC, and 0.5Kg binder, and is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s; the assembly block adopts a new booster ring design, and the booster ring uses ceramic materials Al2O3 and SiC as main raw materials. Both Al2O3 and SiC have high hardness and are resistant to high temperatures, which can achieve the purpose of increasing and stabilizing pressure.
[0042] The sealing ring is made of 50 kg of pyrophyllite powder, 10 kg of dolomite powder, 5 kg of clay powder and 0.5 kg of binder, and is pressed by a four-column hydraulic press at 5 MPa and maintained at a pressure of 30 seconds.
[0043] Conductive alloy pads are made of recycled hard alloy top hammers, ball-milled to 5-10um, pre-pressed, and sintered at 1300℃ for 10 minutes.
[0044] The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
[0045] Example 2: The pyrophyllite block is composed of pyrophyllite particles and a ceramic binder. The pyrophyllite powder is crushed to below 100 mesh, 10% of a hydrophilic ceramic binder is added, and it is pressed by a 150T four-column hydraulic press at 50MPa and maintained at a pressure of 30s, and then baked in a high-temperature oven at 800°C for 5h to form.
[0046] The liner pipe is made of 90Kg dolomite powder, 20Kg MgO powder and 20Kg Al2O3 powder, which are pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s.
[0047] The voltage regulator tube is a three-section tube, the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
[0048] The ring-shaped heating tube is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0049] The isolation tube is made of 70 kg of NaCl powder less than 100 mesh, 5 kg of Al2O3 powder less than 200 mesh, 5 kg of ZrO2 powder less than 200 mesh, 5 kg of SiC powder less than 200 mesh, and 2 kg of resin adhesive.
[0050] The isolation plate is made of the same materials as the isolation tube, consisting of 70 kg of NaCl powder less than 100 mesh, 5 kg of Al2O3 powder less than 200 mesh, 5 kg of ZrO2 powder less than 200 mesh, 5 kg of SiC powder less than 200 mesh, and 2 kg of resin adhesive.
[0051] The metal tube is made of 15Kg of 1um-10um Ni powder, 20Kg of 10um-50um Zr powder, 20Kg of 10um-50um Fe powder, 10Kg of 10um-50um Mn powder, and 10Kg of 10um-50um Mo powder. The mixed powder is hot-pressed and sintered at 1800°C for 70 minutes.
[0052] The heating plate is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0053] The metal sheet material is made of three metal powders, Ti, Mo, and Cr, with contents of 60%, 25%, and 15% respectively, and is sintered at 1800°C for 70 minutes.
[0054] The booster ring is made of 90 kg of Al2O3, 20 kg of SiC, and 1 kg of binder, and is pressed by a four-column hydraulic press at 5 MPa and maintained at a pressure of 30 seconds.
[0055] The sealing ring is made of 70Kg of pyrophyllite powder, 20Kg of dolomite powder, 10Kg of clay powder and 1Kg of binder, and is pressed by a four-column hydraulic press at 5MPa and maintaining pressure for 30s.
[0056] Conductive alloy pads are made of recycled hard alloy top hammers, ball-milled to 5-10um, pre-pressed, and sintered at 1500℃ for 15 minutes.
[0057] The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
[0058] Example 3: The pyrophyllite block is composed of pyrophyllite particles and a ceramic binder. The pyrophyllite powder is crushed to below 100 mesh, 7.5% of a hydrophilic ceramic binder is added, and it is pressed by a 120T four-column hydraulic press at 40MPa, maintaining a pressure of 30s, and then baked in a high-temperature oven at 500°C for 5h to form.
[0059] The liner pipe is made of 75Kg dolomite powder, 15Kg MgO powder and 15Kg Al2O3 powder, which are pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s.
[0060] The voltage regulator tube is a three-section tube, the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
[0061] The ring-shaped heating tube is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0062] The isolation tube is made of 60Kg of NaCl powder less than 100 mesh, 4Kg of Al2O3 powder less than 200 mesh, 4Kg of ZrO2 powder less than 200 mesh, 4Kg of SiC powder less than 200 mesh, and 1.2Kg of resin adhesive.
[0063] The isolation plate is made of the same materials as the isolation tube, consisting of 60 kg of NaCl powder less than 100 mesh, 4 kg of Al2O3 powder less than 200 mesh, 4 kg of ZrO2 powder less than 200 mesh, 4 kg of SiC powder less than 200 mesh, and 1.2 kg of resin adhesive.
[0064] The metal tube is made of 13Kg of 1um-10um Ni powder, 15Kg of 10um-50um Zr powder, 15Kg of 10um-50um Fe powder, 8Kg of 10um-50um Mn powder, and 8Kg of 10um-50um Mo powder. The mixed powder is hot-pressed and sintered at 1550°C for 50 minutes.
[0065] The heating plate is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0066] The metal sheet material is made of Ti, Mo, and Cr metal powders with contents of 60%, 25%, and 15% respectively, and is sintered at 1550°C for 50 minutes.
[0067] The booster ring is made of 80Kg Al2O3, 15Kg SiC, and 0.8Kg binder, and is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s;
[0068] The sealing ring is made of 60 kg of pyrophyllite powder, 15 kg of dolomite powder, 8 kg of clay powder and 0.8 kg of binder, and is pressed by a four-column hydraulic press at 5 MPa and maintained at a pressure of 30 seconds.
[0069] Conductive alloy pads are made of recycled hard alloy top hammers, ball-milled to 5-10um, pre-pressed, and sintered at 1400℃ for 13 minutes.
[0070] The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
[0071] Example 4: The pyrophyllite block is composed of pyrophyllite particles and a ceramic binder. The pyrophyllite powder is crushed to below 100 mesh, 5% of a hydrophilic ceramic binder is added, and it is pressed by a 130T four-column hydraulic press at 50MPa and maintained at a pressure of 30s, and then baked in a high-temperature oven at 800°C for 5h to form.
[0072] The liner pipe is made of 60Kg dolomite powder, 20Kg MgO powder and 15Kg Al2O3 powder, which is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s.
[0073] The voltage regulator tube is a three-section tube, the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
[0074] The ring-shaped heating tube is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0075] The isolation tube is made of 70 kg of NaCl powder less than 100 mesh, 3 kg of Al2O3 powder less than 200 mesh, 4 kg of ZrO2 powder less than 200 mesh, 5 kg of SiC powder less than 200 mesh, and 2 kg of resin adhesive.
[0076] The isolation plate is made of the same materials as the isolation tube, consisting of 70 kg of NaCl powder less than 100 mesh, 4 kg of Al2O3 powder less than 200 mesh, 3 kg of ZrO2 powder less than 200 mesh, 5 kg of SiC powder less than 200 mesh, and 0.5 kg of resin adhesive.
[0077] The metal tube is made of 15Kg of 1um-10um Ni powder, 13Kg of 10um-50um Zr powder, 10Kg of 10um-50um Fe powder, 10Kg of 10um-50um Mn powder, and 7Kg of 10um-50um Mo powder. The mixed powder is hot-pressed and sintered at 1300°C for 40 minutes.
[0078] The heating plate is made of flake graphite with a purity of more than 99.9% and a size less than 40 meshes, and is formed and pressed in one step.
[0079] The metal sheet material is made of three metal powders, Ti, Mo, and Cr, with contents of 60%, 25%, and 15% respectively, and is sintered at 1400°C for 30 minutes.
[0080] The booster ring is made of 75 kg of Al2O3, 10 kg of SiC, and 1 kg of binder, and is pressed by a four-column hydraulic press at 5 MPa and maintained at a pressure of 30 seconds;
[0081] The sealing ring is made of 50 kg of pyrophyllite powder, 18 kg of dolomite powder, 5 kg of clay powder and 0.9 kg of binder, and is pressed by a four-column hydraulic press at 5 MPa and maintained at a pressure of 30 seconds.
[0082] Conductive alloy pads are made of recycled hard alloy top hammers, ball-milled to 5-10um, pre-pressed, and sintered at 1400℃ for 15 minutes.
[0083] The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
[0084] The method for preparing a composite sheet by using the above-mentioned diamond composite sheet assembly block for coal fields is used to place the core body into the heating cavity of the assembly block. Each heating cavity can hold 4 core bodies, and the core bodies are separated by spacers, and one spacer is placed at each end of the outermost core body. The assembly block is placed in a six-sided top press for heating;
[0085] In the first stage, the temperature is heated to 300-400℃ for 10-50s and kept warm for 10-60s; the apparent pressure increases from 0MPa to 50-70MPa;
[0086] The second stage is heating to 800-1000℃ for 10-50s and keeping warm for 10-60s; the apparent pressure is maintained at 80-105MPa;
[0087] In the third stage, the temperature drops rapidly to 200-300℃ within 1-5s and is kept warm for 10-60s; the apparent pressure is maintained at 80-105MPa;
[0088] The fourth stage is heating to 1500℃-1800℃ for 10-60s and keeping warm for 100-150s; the apparent pressure is maintained at 80-105MPa;
[0089] In the final stage, the heating is stopped and the temperature is lowered for 180-240s; the pressure is slowly reduced, the pressure is released, the assembly block is taken out, and the prepared composite sheet is taken out from the assembly block.
[0090] The new structure of the annular heating tube has 3 to 5 cavities, which improves the efficiency by more than 6 times compared with the conventional single-hole heating tube. The larger contact surface area of the annular heating tube reduces the temperature gradient of the top and middle core layers from 50-100°C of the traditional technology to 30-50°C, improving the low efficiency of conventional diamond composite heating tubes used in coal fields.
[0091] Figure 4 As shown, in the first stage, the temperature is heated to T1 (300-400°C) for 10-50s and kept warm for 10-60s; the apparent pressure increases from 0MPa to 50-70MPa, which mainly serves to break and refine the diamond particles and better fill the coarse and fine particles.
[0092] In the second stage, the temperature is heated to T2 (800-1000℃) for 10-50s and kept warm for 10-60s; the apparent pressure is maintained at 80-105MPa; the main function is to accelerate the graphitization of the diamond surface so that the binder can better infiltrate the diamond surface, and at the same time enable the isolation tube to effectively move the liquid phase to achieve isostatic pressure in the assembly block.
[0093] In the third stage, the temperature drops rapidly to T3 (200-300℃) within 1-5s and is kept warm for 10-60s; the apparent pressure is maintained at 80-10SMPa; the rapid cooling mainly makes the assembly components more tightly bonded, while releasing stress and reducing internal stress.
[0094] The fourth stage is to heat to T4 (1500℃-1800℃) for 10-60s and keep warm for 100-150s; the apparent pressure is maintained at 80-105MPa; this stage is a high temperature and high pressure stage, the main function of which is to make the binder fully diffuse, and at the same time make the activated diamond surface fully react with the binder to form more DD bonds.
[0095] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A diamond composite sheet assembly block for coalfield, characterized in that: It comprises a talc block with an embedded lining tube, a voltage-stabilizing tube is installed inside the lining tube, a ring-shaped heating tube is installed inside the voltage-stabilizing tube, 3-5 heating cavities are opened inside the ring-shaped heating tube, and each heating cavity is installed with an isolation tube, a metal tube for placing a core body is installed inside the isolation tube, a heating plate, a metal plate, a boosting ring and a sealing ring are sequentially arranged at the upper and lower ends of the lining tube from the inside to the outside, a conductive steel ring is arranged inside the boosting ring and the sealing ring, and a conductive alloy pad is arranged at the outer end of the conductive steel ring.
2. The diamond composite sheet assembly block for coalfield according to claim 1, characterized in that: The pyrophyllite block is composed of pyrophyllite particles and ceramic binder. The pyrophyllite powder is crushed to below 100 meshes, 5%-10% of hydrophilic ceramic binder is added, and it is pressed by a 100T-150T four-column hydraulic press at 30-50MPa and maintained at a pressure of 30s, and then baked in a high-temperature oven at 200℃-800℃ for 5h to form.
3. The diamond composite sheet assembly block for coalfield according to claim 2, characterized in that: The inner lining pipe is made of 60-90 parts of dolomite powder, 10-20 parts of MgO powder and 10-20 parts of Al2O3 powder by pressing with a four-column hydraulic press at 5MPa and maintaining the pressure for 30s.
4. The diamond composite sheet assembly block for coalfield according to claim 3, characterized in that: The voltage-stabilizing tube is a three-section tube, wherein the upper and lower sections are pyrophyllite tubes, and the middle section is a MgO tube.
5. The diamond composite sheet assembly block for coalfield according to claim 4, characterized in that: The annular heating tube is formed by one-step molding and pressing of flake graphite with a purity of more than 99.9% and a mesh size less than 40.
6. The diamond composite sheet assembly block for coalfield according to claim 5, characterized in that: The isolation tube is made of 50-70 parts of NaCl powder less than 100 meshes, 3-5 parts of Al2O3 powder less than 200 meshes, 3-5 parts of ZrO2 powder less than 200 meshes, 3-5 parts of SiC powder less than 200 meshes, and 0.5-2 parts of resin binder.
7. The diamond composite sheet assembly block for coalfield according to claim 6, characterized in that: The metal tube is made of 10-15 parts of 1um-10umNi powder, 10-20 parts of 10um-50umZr powder, 10-20 parts of 10um-50umFe powder, 5-10 parts of 10um-50umMn powder and 5-10 parts of 10um-50umMo powder. The mixed powder is hot-pressed and sintered at 1300-1800°C for 30-70 minutes.
8. The diamond composite sheet assembly block for coalfield according to claim 1, characterized in that: The heating plate is made of flake graphite with a purity of >99.9% and less than 40 mesh, which is pressed in one step; The metal sheet material is made of three metal powders of Ti, Mo and Cr with contents of 60%, 25% and 15% respectively, and is sintered at 1300-1800°C for 30-70 minutes; The booster ring is made of 70-90 parts of Al2O3, 10-20 parts of SiC, and 0.5-1 parts of a binder, and is pressed by a four-column hydraulic press at 5MPa and maintained at a pressure of 30s; The sealing ring is made of 50-70 parts of pyrophyllite powder, 10-20 parts of dolomite powder, 5-10 parts of clay powder and 0.5-1 part of binder, and is pressed by a four-column hydraulic press at 5MPa and maintaining pressure for 30s.
9. The diamond composite sheet assembly block for coalfield according to claim 8, characterized in that: The conductive alloy pad is made of recycled hard alloy top hammer material, which is ball-milled to 5-10um, pre-pressed, and sintered at 1300-1500°C for 10-15 minutes. The inner wall of the conductive steel ring is paved with dolomite powder with a thickness of 1-3 mm and high-temperature ceramic powder with a thickness of 1-3 mm in sequence.
10. A method for preparing a compact using the diamond compact assembly block for coalfields according to any one of claims 1 to 9, characterized in that: Place the core into the heating cavity of the assembly block. Each heating cavity can hold 4 cores. The cores are separated by spacers, and one spacer is placed at each end of the outermost core. Place the assembly block in a six-sided press for heating. In the first stage, the temperature is heated to 300-400℃ for 10-50s and kept warm for 10-60s; the apparent pressure increases from 0MPa to 50-70MPa; The second stage is heating to 800-1000℃ for 10-50s and keeping warm for 10-60s; the apparent pressure is maintained at 80-105MPa; In the third stage, the temperature drops rapidly to 200-300℃ within 1-5s and is kept warm for 10-60s; the apparent pressure is maintained at 80-105MPa; The fourth stage is heating to 1500℃-1800℃ for 10-60s and keeping warm for 100-150s; the apparent pressure is maintained at 80-105MPa; In the final stage, the heating is stopped and the temperature is lowered for 180-240 seconds; the pressure is slowly reduced, the pressure is released, the assembly block is taken out, and the prepared composite sheet is taken out from the assembly block.